»Obravnava, kakoršna še ni bila v Ljubljani« - Smiljanić, Ivan (Prispevki za novejšo zgodovino, 2024)
The contribution presents the financial affair of a wood merchant’s wife, Terezija Aristoteles, in Ljubljana in the 1870s. Aristoteles took a loan from one of Ljubljana’s female brokers who, for steep interest rates, mediated the borrowing of money obtained from moneylenders. In doing so, Aristoteles got heavily into debt and resorted to fraud to keep borrowing increasing sums of money. Once her actions were revealed, a high-profile trial at the Ljubljana Court followed in February 1874, attracting a lot of interest not only from the Ljubljana citizens but also from the Slovenian and Austrian press, mainly because most of the perpetrators and victims involved were female. The public opinion did not favour either Aristoteles or the aggrieved moneylenders, who were seen as exploiters preying on those in need. Aristoteles and her broker were sentenced to two years in prison.
Keywords: Austria-Hungary; Avstro-Ogrska; brokering; Deželno sodišče v Ljubljani; financial fraud; finančna goljufija; mešetarjenje; Regional Court in Ljubljana; Terezija Aristoteles